Association of serum amylase and lipase levels in newly diagnosed type 2 diabetes mellitus - R., Hareesh; K. V., Harish; Savith, Akshatha (International Journal of Advances in Medicine, 2021)
Background: Type 2 diabetes mellitus is a chronic metabolic disorder due to insulin resistance caused by destruction of beta cells of pancreas. Insulin resistance in newly diagnosed type 2 diabetes mellitus patients leads to hyperglycemia. Serum amylase and lipase levels is an exocrine enzyme produced by acinar cells of pancreas. Altered levels of serum amylase and lipase leads to endocrine disorders, metabolic syndrome and diabetes mellitus. Methods: This is a case-control study conducted in Akash Institute of Medical Sciences, A total 100 subjects (50 cases and 50 controls). All the subjects included after informed consent, blood samples are collected from the all the subjects. The serum amylase and was estimated by using enzymatic commercial available kits and fasting blood sugar (FBS), post-parandial blood sugar (PPBS), renal function test (RFT) and liver function test (LFT) was also estimated by laboratory standard methods. Results: This study evaluated the FBS, PPBS, RFT, LFT, Amylase and Lipase levels in patients with newly diagnosed type 2 diabetes mellitus patients and compare them with healthy controls. The serum amylase and lipase levels more significantly elevated in newly diagnosed type 2 diabetes mellitus patients and compared with the healthy controls. The study also found that significantly elevated levels of FBS, PPBS, RFT and LFT in newly diagnosed type 2 diabetes mellitus patients and compared with the healthy controls, The statistically significant levels of serum amylase and lipase levels in patients with newly diagnosed type 2 diabetes mellitus when compared with the controls (p=0.0001). Conclusions: The study suggesting that to estimation of serum amylase and lipase levels in newly diagnosed type 2 diabetes mellitus patients useful for early detection of diabetes mellitus and its complications. Because elevated levels of serum amylase and lipase in patients with newly diagnosed type 2 diabetes mellitus, these levels are positively correlated with the FBS and PPBS.